2019
DOI: 10.1590/rbz4820160377
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of curimba (Prochilodus lineatus) embryos using different concentrations of dimethyl sulphoxide and methanol

Abstract: This study aimed to evaluate the effect of using different concentrations (5, 7.5, 10, and 12.5%) of two permeating cryoprotectants, dimethyl sulphoxide (DMSO) and methanol, on Prochilodus lineatus embryos while being subjected to cooling for 2, 4, 6, and 8 h at 4 °C. We analyzed the hatching rate, viable larvae, and counts of hatched and spoiled eggs and those that did not complete their development after cooling. We observed a significant interaction among variables, permeable cryoprotectant concentration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Introduction Development of effective techniques for cryopreservation of fish eggs and embryos could provide a valuable tool for the propagation of economically important and endangered species alike. The access to cryopreserved embryos in periods when natural spawning does not occur, could allow an increase in commercial production and conservation of rheophilic (Bozkurt, 2018;Machado et al, 2019) or any species of fish.…”
mentioning
confidence: 99%
“…Introduction Development of effective techniques for cryopreservation of fish eggs and embryos could provide a valuable tool for the propagation of economically important and endangered species alike. The access to cryopreserved embryos in periods when natural spawning does not occur, could allow an increase in commercial production and conservation of rheophilic (Bozkurt, 2018;Machado et al, 2019) or any species of fish.…”
mentioning
confidence: 99%
“…Studies with fish have demonstrated the positive effects of refrigeration associated with the use of cryoprotectants among which stands out dimethylsulphoxide (DMSO), which is widely used for cooling embryos of Prochilodus lineatus , promoting conservation and raising the hatching rate of larvae (Machado et al, 2019) at low concentrations. Dimethylsulphoxide (DMSO) also prolonged the motility rate up to 13 days of refrigeration, increasing the fertilization capacity of semen from Oncorhynchus mykiss (Ubilla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The streaked prochilod Prochilodus lineatus (Prochilodontidae, Characiformes) is a migratory neotropical fish with a large distribution in the main hydrographic basins of South America (Castro & Vari, 2004). This species is well adapted to captivity and has been used in reproduction studies (Machado et al, 2019; Miliorini et al, 2011; Paula et al, 2019), proving it can be used as a model species for the study of other neotropical fish species, which are considered endangered. The annual migration and spawn of the P. lineatus occur during the rainy months when water levels rise, water temperatures are higher, and the day length is longer (Vazzoler et al, 1997).…”
Section: Introductionmentioning
confidence: 99%